Astronomic Causes of Global Climate Change - Akhmedov, Sh.A.; Akhmedova, M. Sh.; Guseynova, G.Sh. (Herald of Azerbaijan Engineering Academy, 2021)
The article studies the analysis of the study of astronomical factors of modern climate change Climate is a generalized characteristic of the state of the natural environment around us. The temperature regime is an important component, which determines many features of the life of the population and the state of the natural environment. Therefore, the problem of climate change and, first of all, its temperature characteristics seems to be significant for modern science and practice. At present, there are noticeable trends in the change in the surface air temperature, the temperature of the ocean surface, the level of the World Ocean, the area of sea ice and permafrost, and the ice mass of mountain glaciers. Finding the reasons for the trends observed in the Earth's climate system means finding an explanation for the observed changes in the Earth's climate. Currently, it is widely assumed that the main cause of global climate change is the "greenhouse" effect, associated mainly with the emission of greenhouse gases determined by the anthropogenic factor (combustion of coal and hydrocarbon fuels). At the same time, there is no doubt that solar radiation is of great importance in the genesis of climate.